Views of violence : representing the Second World War in German and European museums and memorials - Echternkamp, Jörg 1963- HerausgeberIn; Jaeger, Stephan 1970- HerausgeberIn; Winter, Jay 1945- VerfasserIn eines Nachworts (Spektrum ;, 2019)
"Twenty-first-century views of historical violence have been immeasurably influenced by cultural representations of the Second World War. Within Europe, one of the key sites for such representation has been the vast array of museums and memorials that reflect contemporary ideas of war, the roles of soldiers and civilians, and the self-perception of those who remember. This volume takes a historical perspective on museums covering the Second World War and explores how these institutions came to define political contexts and cultures of public memory in Germany, across Europe, and throughout the world."--Provided by publisher